Factors influencing healthcare workers’ compliance with personal protective equipment guidelines in long-term care during the COVID-19 pandemic—A theory-based mixed-methods study - Anna-Leena Lohiniva; Jaana Marija Lehtinen; Dinah Arifulla; Jukka Ollgren; Pekka Nuorti; Outi Lyytikäinen (PLoS ONE, 2025)
Introduction Residents and healthcare workers in long-term care facilities are at increased risk of infection during respiratory epidemics. Proper compliance with infection prevention and control measures is therefore paramount. Our study aimed to uncover and understand factors influencing compliance with personal protective equipment guidelines among healthcare workers in long-term care facilities in Finland during the COVID-19 pandemic. Methodology We conducted a mixed-methods study by using the methods and framework of behavioral insights, specifically the Theoretical Domains Framework. Data were collected through a web-based survey and qualitative in-depth telephone interviews using convenience sampling. Participants for the anonymous survey were recruited through regional infection control experts during May-June 2022. Survey data were analyzed by using logistic regression; difficulties in complying with personal protective equipment guidelines were the outcome. Volunteer survey respondents were interviewed, and the data were analyzed thematically. Results A total of 373 healthcare workers participated in the survey; 56% had received personal protective equipment training. Two domains of the Theoretical Domains Framework were associated with experiencing difficulties in compliance with the personal protective barriers: organization linked with insufficient human resources and the presence of negative emotions linked with stress. Twenty-two healthcare workers participated in the interviews which resulted in the identification of several themes, suggesting how insufficient human resources and negative emotions affected personal protective equipment use and the type of coping mechanism that healthcare workers used to overcome these barriers. Conclusions The behavioral insights derived from our study can contribute to enhanced healthcare worker compliance with personal protective equipment use. These findings underscore the importance of access to training, interventions addressing stress and ensuring sufficient workforce.